A Qualitative Report on the Subjective Experience of Intravenous Psilocybin Administered in an fMRI Environment. - Turton,SP; Nutt,DJ; Carhart-Harris,RL (Current Drug Abuse Reviews, 2014)
Background: This report documents the phenomenology of the subjective experiences of 15 healthy psychedelic experienced volunteers who were involved in a functional magnetic resonance imaging (fMRI) study that was designed to image the brain effects of intravenous psilocybin. Methods: The participants underwent a semi-structured interview exploring the effects of psilocybin in the MRI scanner. These interviews were analysed by Interpretative Phenomenological Analysis. The resultant data is ordered in a detailed matrix, and presented in this paper. Results: Nine broad categories of phenomenology were identified in the phenomenological analysis of the experience; perceptual changes including visual, auditory and somatosensory distortions, cognitive changes, changes in mood, effects of memory, spiritual or mystical type experiences, aspects relating to the scanner and research environment, comparisons with other experiences, the intensity and onset of effects, and individual interpretation of the experience. Discussion: This article documents the phenomenology of psilocybin when given in a novel manner (intravenous injection) and setting (an MRI scanner). The findings of the analysis are consistent with previous published work regarding the subjective effects of psilocybin. There is much scope for further research investigating the phenomena identified in this paper.